2022
DOI: 10.1063/5.0082161
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast vibrational excitation transfer on resonant antenna lattices revealed by two-dimensional infrared spectroscopy

Abstract: High-quality lattice resonances in arrays of infrared antennas operating in an open-cavity regime form polariton states by means of strong coupling to molecular vibrations. We studied polaritons formed by carbonyl stretching modes of (poly)methyl methacrylate on resonant antenna arrays using femtosecond 2DIR spectroscopy. At a normal incidence of excitation light, doubly-degenerate antenna-lattice resonances (ALR) form two polariton states: a lower polariton and an upper polariton. At an off-normal incidence g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…After the first report of the ultrafast IR pump–probe study of MVPs by Dunkelberger, Owrutsky, and co-workers and inspired by theoretical works, our group collaborated with the Naval Research Laboratory group to implement 2D IR spectroscopy to study polariton dynamics. , We showed that 2D IR spectroscopy has unique capabilities to resolve dark modes from polariton states. This method has since been adopted to study pure polaritonic responses and polaritons in open cavity systems. …”
Section: D Ir Spectroscopy For Vibrational Polaritonsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first report of the ultrafast IR pump–probe study of MVPs by Dunkelberger, Owrutsky, and co-workers and inspired by theoretical works, our group collaborated with the Naval Research Laboratory group to implement 2D IR spectroscopy to study polariton dynamics. , We showed that 2D IR spectroscopy has unique capabilities to resolve dark modes from polariton states. This method has since been adopted to study pure polaritonic responses and polaritons in open cavity systems. …”
Section: D Ir Spectroscopy For Vibrational Polaritonsmentioning
confidence: 99%
“…This method has since been adopted to study pure polaritonic responses and polaritons in open cavity systems. 52 54 …”
Section: D Ir Spectroscopy For Vibrational Polaritonsmentioning
confidence: 99%
“…5 Ultrafast spectroscopy of polaritons provides a unique window to reveal how energy of polariton states redistributes into molecular modes and influences the chemistry. Significant works using pump-probe and two-dimensional infrared (2D IR) spectroscopy 6,7 have shown that polaritons can open new pathways for inter-and intra-molecular vibrational energy transfer 8 , as well as hinder isomerization events 9 . Furthermore, results from our group previously showed that for W(CO)6 based MVPs, excited LP and UP underwent different dynamics: UP decayed rapidly and exponentially to the first excited state of dark modes, while LP first transferred to an intermediate state before relaxing to the first excited dark modes, which manifested as an initial rise and then a decay.…”
mentioning
confidence: 99%
“…Experimentally, an open cavity was constructed with a high-quality antenna-lattice resonance (ALR) of the half-wavelength infrared antenna array, 38 , 39 where individual dipolar antenna resonances couple to the in-plane lattice diffraction order. 40 , 41 Unlike the commonly used Fabry–Perot-style optical cavities, in our experiments, the optical extinction occurs only at the ALR frequency while the nearby spectral region remains transparent, thus allowing direct spectroscopic access both to the polaritons and to the reservoir transitions.…”
mentioning
confidence: 99%
“…Experimentally, an open cavity was constructed with a high-quality antenna-lattice resonance (ALR) of the half-wavelength infrared antenna array, , where individual dipolar antenna resonances couple to the in-plane lattice diffraction order. , Unlike the commonly used Fabry–Perot-style optical cavities, in our experiments, the optical extinction occurs only at the ALR frequency while the nearby spectral region remains transparent, thus allowing direct spectroscopic access both to the polaritons and to the reservoir transitions . A 3 × 3 mm nearly defect-free antenna array was fabricated by means of electron-beam lithography on a CaF 2 window. The gold antennas (dimensions of 0.75 × 0.2 × 0.07 μm) were arranged in a rectangular lattice with a longitudinal period (along the antenna axis) of D L = 1.35 μm and a transverse period of D T = 3.8 μm, as shown in Figure a (inset).…”
mentioning
confidence: 99%